2015
DOI: 10.3109/13880209.2014.942789
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of pentylenetetrazole-induced seizure threshold by chronic administration of ginger (Zingiber officinale) extract in male mice

Abstract: Context: Zingiber officinale Roscoe (Zingiberaceae), or ginger, used in traditional Chinese medicine, has antioxidant activity and neuroprotective effects. The effects of this plant on clonic seizure have not yet been studied. Objective: The present study evaluated the anticonvulsant effect of ginger in a model of clonic seizures induced with pentylenetetrazole (PTZ) in male mice. Materials and methods: The anticonvulsant effect of Z. officinale was investigated using i.v. PTZ-induced seizure models in mice. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 43 publications
(47 reference statements)
0
12
0
Order By: Relevance
“…Moreover, their beneficial effects were previously reported in Parkinson’s disease, Alzheimer’s disease [ 48 , 49 , 50 , 51 ], depression [ 52 , 53 ], stress [ 54 ], and anxiety [ 55 , 56 ] in animal models. The anticonvulsant effect of ginger extract in the intravenous PTZ seizure test in mice has also been reported [ 24 , 25 ]. However, neither the influence of individual ingredients of the ginger extracts, mainly gingerols and shogaols, nor the mechanism of anticonvulsant activity of ginger extracts/constituents has been previously investigated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, their beneficial effects were previously reported in Parkinson’s disease, Alzheimer’s disease [ 48 , 49 , 50 , 51 ], depression [ 52 , 53 ], stress [ 54 ], and anxiety [ 55 , 56 ] in animal models. The anticonvulsant effect of ginger extract in the intravenous PTZ seizure test in mice has also been reported [ 24 , 25 ]. However, neither the influence of individual ingredients of the ginger extracts, mainly gingerols and shogaols, nor the mechanism of anticonvulsant activity of ginger extracts/constituents has been previously investigated.…”
Section: Discussionmentioning
confidence: 99%
“…The latter components, called gingerols and shogaols, which are responsible for the pungent taste of the rhizome, were recently proven to cross the blood–brain barrier [ 19 ] and exhibit central activity that includes the monoamine oxidase A (MAO-A) inhibition [ 20 ], migraine relief [ 21 ], dendritic cell activity amelioration [ 22 ], and neuroprotective action [ 23 ]. Previously, Zingiber officinale hydroethanolic extract was shown to exert antiseizure activity in the acute intravenous PTZ test and PTZ-kindling model in mice, but active constituents responsible for this effect have not been determined [ 24 , 25 ]. More recently, using the PTZ-induced hyperlocomotion assay in larval zebrafish, Brillatz et al [ 26 ] indicated that the hexane extract of Zingiber purpureum possesses anticonvulsant properties, with two active phenylbutenoids, i.e., trans - and cis -banglene, being responsible for this effect.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, the PTZ model was used to induce epileptic kindling and cognition deficit, as it is a wellestablished animal model which simulates clinical epilepsy (Golechha et al, 2010;Hosseini & Mirazi, 2015). PTZ kindling in rodents have been associated with neuronal damage in the hippocampus due to free radicals generation which results in memory loss (Pohle et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…The extraction method was performed according to the references and the previous works. 10 This means that about 1000 g of the leaves of the specified plant got prepared, cleaned, and dried in the shade and by the mechanical crushers changed into powder. To prepare the ethanol extract, the powder of the plant was soaked in 1000 mL of ethanol 60% for 24 hours in three times; then, the elicited mixture was filtered and concentrated in vacuum at a temperature of 45°C with the help of a Rotary device (EYEL A, Japan; the amount of the obtained dried extract was 37.8 percent).…”
Section: Preparing the Herb And The Extractmentioning
confidence: 99%